1. f(x) = 4
(√5 - x)
Note: 5 - x is all squared.
2. f(x) = 2x
x - 2
3. f(x) = √x + 2
3
Is it all squared or all in the square root? A clearer way of writing that would be 4/√(5- x). Use parentheses!
That is equal to $\displaystyle 4(5- x)^{-1/2}$. Use the "power rule" (derivative of $\displaystyle x^n$ is $\displaystyle n x^{n-1}$ and the chain rule.
f(x)= 2x/(x- 2). Use the quotient rule![SIZE=5]
2. f(x) = 2x
x - 2
$\displaystyle (1/3)(x+2)^{1/2}$3. f(x) = √x + 2
3
Again, "power rule" and "chain rule".
i understand the concept of rules. but the problem i am having with these questions is that i was asked to find the derivative using the definition. i know the definition is
f`(x) = f( x + h) - f(x) Żall over- h
but when i place the equations into the definition i cannot get the same answer as the rules. there is something i am doing wrong and i dont know what..
please help..